2018
DOI: 10.3390/ijms19092566
|View full text |Cite
|
Sign up to set email alerts
|

Telocinobufagin, a Novel Cardiotonic Steroid, Promotes Renal Fibrosis via Na+/K+-ATPase Profibrotic Signaling Pathways

Abstract: Cardiotonic steroids (CTS) are Na+/K+-ATPase (NKA) ligands that are elevated in volume-expanded states and associated with cardiac and renal dysfunction in both clinical and experimental settings. We test the hypothesis that the CTS telocinobufagin (TCB) promotes renal dysfunction in a process involving signaling through the NKA α-1 in the following studies. First, we infuse TCB (4 weeks at 0.1 µg/g/day) or a vehicle into mice expressing wild-type (WT) NKA α-1, as well as mice with a genetic reduction (~40%) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 65 publications
0
23
0
Order By: Relevance
“…However, unintended effects of high concentrations of these hormones potentially contribute to disease progression [ 10 , 29 , 50 , 51 , 52 ]. Long-lasting elevation of CTS may produce “off-target” effects [ 13 ], potentially including the profibrotic and the proinflammatory effects of these hormones [ 53 ]. Hence, chronic elevation of CTS signaling through NKA has implications not only for natriuretic response to high salt and volume load, but also for pathological adaptation to these conditions [ 54 ].…”
Section: Cardiotonic Steroids: Nka Ligands Brokering the Sodium Trmentioning
confidence: 99%
“…However, unintended effects of high concentrations of these hormones potentially contribute to disease progression [ 10 , 29 , 50 , 51 , 52 ]. Long-lasting elevation of CTS may produce “off-target” effects [ 13 ], potentially including the profibrotic and the proinflammatory effects of these hormones [ 53 ]. Hence, chronic elevation of CTS signaling through NKA has implications not only for natriuretic response to high salt and volume load, but also for pathological adaptation to these conditions [ 54 ].…”
Section: Cardiotonic Steroids: Nka Ligands Brokering the Sodium Trmentioning
confidence: 99%
“…Previous in vivo studies have also demonstrated morphological evidence of steatohepatitis, induced by the cardiotonic steroid mediated activation of Na/K-ATPase signaling [40], along with alteration of hepatic lipid accumulation markers, fibrosis, inflammatory markers and mitochondrial fatty acid oxidation markers [40]. Since the activation of Na/K-ATPase signaling is mediated by cardiotonic steroid [15,41,42], the further downstream activation of this signaling cascade has also been shown to increase Homeostatic Model Assessment of Insulin Resistance (HOMA-IR) levels and blood glucose tolerance in high fat diet fed mice [43], suggesting an association of cardiotonic steroids with diabetes. Hence, cardiotonic steroids might be one of the possible mechanisms that may aggravate NAFLD.…”
Section: Introductionmentioning
confidence: 94%
“…Apart from these well-established mechanisms of hepatic fibrosis and disease progression, cumulative clinical and experimental evidence present in the literature suggests a role of cardiotonic steroids in mediating prooxidant and profibrotic effects in hepatic tissue [15][16][17][18][19][20][21][22]. While the hepatic tissue is a primary site for the maintenance of cholesterol homeostasis [23], studies have suggested an important role of cardiotonic steroids in regulation of cholesterol biosynthesis [24,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated levels of circulating CTS potentially contribute to disease progression, such as in various chronic inflammatory conditions like obesity, hypertension, NASH, cardiovascular disease, and further stimulate the proinflammatory and profibrotic response [91][92][93]99,102,[161][162][163][164]. Numerous studies have examined the role of the Na/K-ATPase ascribed by the scaffolding and signaling function in mediating organ fibrosis [91,101,165]. Many in vivo and in vitro studies have shown that CTS mediate signal transduction through Na/K-ATPase that induce signaling cascades, directly involved in the development of fibrosis in different tissues, including heart, kidney and vasculature [91,92,101,166,167].…”
Section: Cardiotonic Steroids Mediated Na/k-atpase Signaling and Fibrmentioning
confidence: 99%